Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U.S.A. - Cruz, Paulo Vilela; Usher, Andrew K.; Jacobus, Luke M. (Zootaxa, 2017)
Paracloeodes Day is a western hemisphere genus with 20 species, but only three of these valid species are known from continental North and Central America. Based on available literature comparisons, species-level identifications of these three species can be difficult. Considering the apparent similarity between them, the main objective of this study was to examine type and other material housed in the Purdue Entomological Research Collection and the University of Minnesota in order to evaluate species status and to elucidate additional diagnostic characters. The evaluation resulted in validation of P. fleeki McCafferty & Lenat, P. lugoi Randolph & McCafferty and P. minutus (Daggy) and the confirmation of P. abditus Day as a junior synonym of P. minutus. Furthermore, we discovered a new species from the type locality of P. minutus. Paracloedes lotor n. sp. is described based on the nymph stage and a putative male imago from the Mississippi River in Minnesota. Paracloeodes lotor n. sp. differs from the other continental North and Central American species of the genus by the apical half of the paraglossa having an abrupt decrease in width (the “subtriangular” condition) in nymphs, and by having the posterior margin of the styliger plate with a small and pointed spine in the male imago. We provide a new identification key for nymphs of the four continental North and Central American species.